(3GdfcJ GdUGajI aj TQM dH GdcGajIs - (3YdGA GdOjf Ydj Hf HGdi GdHONTis; (3YHO Gddg Hf YeQ Hf eMeO Hf Ydj GdTjQGRj, CHh SYjO CHh GdNjQ fGUQ GdOjf GdHjVGhj,J (B685 (3g` s
(3ChdgG (B:s
(3HGSec jG ef QaY CYdGe GdSeGA HbOQJg , hfUH ai CbWGQ GdCQV OdGFd YRJg CeG HYO adeG hLOJ GdcJGH GdefShH Edi GdHjVGhi cJGHkG aGNQkG jMGci OQI GdJGL hbUOJ Cf CTQMg hSejJg HGdfcJ GdUGajI ai TQM dH GdcGajI s
(3BNQgG (B:s
(3hGddg OQ GdeUfa MjK bUO HQGYI GdNJGe MjK LYd BNQ GdcdGe ai JMbjb gPG GdeQGe bhdg hbakG GdOGd Ydi GdEfbVGA hGdJeGe s
(3HgG fXGe GdJYbjHIs
(3HChdg hbajI HGSe eMeO SYjO Hf eMeO Hc EjGS GdOeSis
(3Ydi UaMI GdZdGa JCQjN HGddZI GdJQcjI SfI (B1007(3g`s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs